Time and energy budgets of wintering Ring-necked Ducks Aythya collaris in Florida, USA - Jeske, Clinton W; Percival, H Franklin (Wildfowl, 1995)
We developed a time budget from 220.5 hours of observations of Ring-necked Ducks wintering on four wetlands in north central Florida. Foraging and resting were the dominant activities occupying 30-40% and 39-42% of the 24-hour period, respectively. Most foraging occurred during the three hour periods following sunrise and preceding sunset. Maintenance behaviour composed 4-9%, swimming 4-8% and alert behaviour 4-7% of diel activities. Other behaviours, including flying, aggression and courtship, were less than 1%. No differences in behaviour partitioning were detected among years or months, or between sexes, but time budgets differed among time periods. Time males spent in alert behaviour was associated with wind direction and habitat type, and time males spent swimming was associated with habitat type. Two methods were used to estimate daily energy expenditure (DEE), which varied from 123 to 169 kcal/bird/day. Ring-necked Ducks would need to consume 3,370-4,170 Hydrilla verticillata tubers per day to meet these energy requirements.